Developmental Offending Patterns: Female Offending Beyond the Reference Category - Gushue, Kelsey (Criminal justice and behavior, 2021)
Compared with young men, justice-involved young women are often characterized by a greater array of risk factors, yet show a more limited pattern of offending. This paradox may be related to risk factors functioning differently not only for male versus female adolescents but also among female adolescents involved in offending. Data were used on 284 girls from the Incarcerated Serious and Violent Young Offender Study to address whether risk factors varied across different offending trajectories modeled between ages 12 and 23. Risk factors measured from self-report interviews were compared across the three trajectories identified. Individual, family, and school risk factors varied across trajectory groups, but not always in ways anticipated. Female offending does not appear to fit neatly within existing developmental criminology theory. Theoretical models should be adapted, or new models developed, to account for the complexities of female offending patterns.